Alloxan-Induced Diabetes Causes Morphological and Ultrastructural Changes in Rat Liver that Resemble the Natural History of Chronic Fatty Liver Disease in Humans - Lucchesi, Amanda Natalia [UNESP]; Cassettari, Lucas Langoni [UNESP]; Spadella, Cesar Tadeu [UNESP] (Hindawi Publishing Corporation, 2015)
Purpose. This study evaluated the long-term effects of alloxan-induced diabetes in rat liver. Methods. Thirty nondiabetic control rats (NC) and 30 untreated diabetic (UD) rats were divided into three subgroups sacrificed after 6, 14, or 26 weeks. Clinical and laboratory parameters were assessed. Fresh liver weight and its relationship with body weight were obtained, and liver tissue was analyzed. Results. UD rats showed sustained hyperglycemia, high glycosylated hemoglobin, and low plasma insulin. High serum levels of AST and ALT were observed in UD rats after 2 weeks, but only ALT remained elevated throughout the experiment. Fresh liver weight was equal between NC and UD rats, but the fresh liver weight/body weight ratio was significantly higher in UD rats after 14 and 26 weeks. UD rats showed liver morphological changes characterized by hepatic sinusoidal enlargement and micro- and macrovesicular hepatocyte fatty degeneration with progressive liver structure loss, steatohepatitis, and periportal fibrosis. Ultrastructural changes of hepatocytes, such as a decrease in the number of intracytoplasmic organelles and degeneration of mitochondria, rough endoplasmic reticulum, and nuclei, were also observed. Conclusion. Alloxan-induced diabetes triggered liver morphological and ultrastructural changes that closely resembled human disease, ranging from steatosis to steatohepatitis and liver fibrosis.